Prevalence and Management of Helminthiasis among Underfives Living with HIV/AIDS at Amana Hospital, Tanzania - Kennedy D. Mwambete MPharm Sci, PhD; Jones Tunzo BPharm; Mary Justin-Temu BPharm, PhD (Journal of the International Association of Providers of AIDS Care, 2013)
Objective: This was a cross-sectional study intended to assess the prevalence and management of helminthiasis (HL) among underfives living with HIV/AIDS (ULHA). Methodology: Clinical histories of ULHA were scrutinized for HIV/AIDS status, antiretroviral therapy (ART), HL prevalence, and their management. Results: About 364 ULHA were studied, 213 (58.5%) were girls and 151 (41.5%) were boys. Of the 364 ULHA, 171 (47.5%) had HL and 64.3% were treated with albendazole (ABZ). Trichuriasis was ascribed to 23.6% of HL. Majority (72.5%) of ULHA had a CD4 count below 200 cells/mm 3 . Direct association was observed between CD4 counts and HL. About 55% ULHA were on lamivudine (3TC)-stavudine (d4T)-nevirapine (NVP; LSN) combination therapy. The ABZ-LSN combination was frequently used for HIV/AIDS and HL management. Conclusion: High prevalence of HL and vivid correlation between HIV status and HL were observed. The LSN-ABZ combination was frequently employed for management of HIV/AIDS and HL. We recommended prompt diagnosis of HL to avoid acceleration of HIV infection to AIDS.